A New Key Exchange Algorithm over a Vlc Indoor Channel - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper proposes a new cryptosystem that combines Diffie-Hellman protocol implemented with hyperelliptic curves over a Galois field GF(2n) with Tree Parity Machine synchronization for a Visible Light Communication indoor channel. The proposed cryptosystem security focuses on overcoming a weakness of neuronal synchronization; specifically, the stimulus vector that is public, which allows an attacker to try to synchronize with one of the participants of the synchronization. Real data receptions of the Visible Light Communication channel are included. In addition, there is an improvement of 115% over a range of 100 ≤ tsync ≤ 400 of the average synchronization time t-sync, compared to the classic Tree Parity Machine synchronization. © 2017 IEEE.